Model for the representation of lgbti+ characters in audiovisual content - Palomino Gámez, Sergio (2022)
The purpose of this paper is to propose and validate a model for the representation of LGBTI+ characters in audiovisual content, which will serve as a tool for content generators to create characters that are in keeping with the reality of this population group and that are appropriate in their representation. In addition to the model, a validation of the model is sought, considering its implementation in a sample of original content from the Netflix streaming platform. In conclusion, it is identified that despite the increasing presence of lgbti+ characters in the media, the representation continues to be biased and stereotyped.